Comparison between outcomes of a sprint test on a wheelchair ergometer and on-court among wheelchair tennis players - Janssen, R.; van Dijk, M.; Rietveld, T.; de Groot, S.; van der Woude, L.; Houdijk, H.; Vegter, R. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The current study compared a wheelchair sprint in the laboratory (lab) on a wheelchair ergometer with a wheelchair sprint on-court in a group of experienced wheelchair tennis players. Nine wheelchair tennis players performed a 10m sprint in the lab, on a computerized wheelchair ergometer, and a 10m sprint on-court, equipped with inertial measurement units. Test duration, mean power output and mean velocity showed no differences between lab and field sprints, peak velocity was consistently higher in the field sprint. Despite methodological differences and experienced rolling resistance between the lab and field sprint, test duration, achieved power output and mean velocity did not differ. Field sprint testing is easier to conduct and provides valuable insights, and lab testing gives a broad additional array of in-depth biomechanical analyses.